Multiple-Perspective and Spatial domains of the Islamic Art - Khan, Mamoona (Ancient Pakistan, 2018)
Multiple-perspective is a novelty introduced by the Muslim artists to represent the spatial domains of reality in its totality. But derogatory remarks are usually attached to this art by western critics, who habitually view things through the lens of corporeal vision. They elevated one, two or three points perspectives as the only way to represent the physical world, ignoring altogether vision beyond the scientific. In order to get a proper comprehension of spatial representation in the Muslim Art, miniature paintings need to be thoroughly analyzed. Thus, multiple points of vision, through which Persian as well as Mughal miniatures are composed, will be explicated in this paper through formal and textual analysis, to investigate true context of its use. Miniature painting being court art, patronized by the ruling classes, is replete with minute details, essential to describe court splendour that would have vanished if veiled under illusions of recession or depth. While multiple-perspective ensures the capacity to retain that splendour and portray tangible and intangible domains of realty. It is the very reason that Muslim artists preferred to remain committed throughout to the path of multiple perspective, once explored by their cerebrating brains.